2018
DOI: 10.1002/anie.201801058
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of a Prodrug by Thioredoxin Reductase Providing a Strategy to Target Cancer Cells

Abstract: Elevated reactive oxygen species and antioxidant defense systems have been recognized as one of the hallmarks of cancer cells. As a major regulator of the cellular redox homeostasis, the selenoprotein thioredoxin reductase (TrxR) is increasingly considered as a promising target for anticancer drug development. The current approach to inhibit TrxR predominantly relies on the modification of the selenocysteine residue in the C-terminal active site of the enzyme, in which it is hard to avoid the off-target effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 56 publications
0
67
0
Order By: Relevance
“…Numerous antitumor agents have been reported to increase ROS production in cancer cells . Different mechanisms have been studied, such as redox cycling and mitochondrial oxidase activation . Our results indicated that the most active gold(I) complex 4 b containing an OA derivative targets TrxR to induce ROS in A2780 cells and activate ROS‐dependent ERS activation.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Numerous antitumor agents have been reported to increase ROS production in cancer cells . Different mechanisms have been studied, such as redox cycling and mitochondrial oxidase activation . Our results indicated that the most active gold(I) complex 4 b containing an OA derivative targets TrxR to induce ROS in A2780 cells and activate ROS‐dependent ERS activation.…”
Section: Resultsmentioning
confidence: 82%
“…Cancer cells generally have higher metabolic demands due to their highly proliferative nature. The thioredoxin system, including thioredoxin reductase (TrxR), thioredoxin (Trx), and NADPH, regulates cellular signal pathways and proliferation . TrxR is the only known physiological enzyme that can catalyze the reduction of oxidized Trx .…”
Section: Introductionmentioning
confidence: 99%
“…By employing characteristic intracellular and surrounding environments of cancer cells, prodrugs that could be selectively activated by cancer cells have attracted increasing interests in the past few years. 14,15 Based on the unique microenvironment of cancer cells, a large number of prodrugs that respond to different stimuli, such as thiols, [16][17][18][19] acidic pH, 20,21 ROS, 13,22,23 enzymes, 24,25 hypoxia 26,27 and light, [28][29][30] have been disclosed with great success in the experimental treatment of various cancer cells. Among different types of prodrugs, exploiting the disul-de scaffold as a trigger unit has been widely adopted, [16][17][18][19]31,32 as cancer cells usually have a higher ability than normal cells to reduce the disulde bond due to the elevated level of antioxidant molecules, such as thioredoxin (Trx), thioredoxin reductase (TrxR) and reduced glutathione (GSH).…”
Section: Introductionmentioning
confidence: 99%
“…31,[39][40][41][42][43] Depending on the ring size, cyclic disuldes/diselenides suffer from signicant ring tension and display different reactivity from acyclic disuldes/diselenides. [44][45][46][47] Encouraged by the recent work on employing a cyclic disulde moiety to construct uorescent probes and prodrugs, 24,44,[48][49][50] we report herein the construction of a seleno-prodrug Se-Gem ( Fig. 1) by introducing a 1,2-diselenolane (ve-membered cyclic diselenide) moiety into the anticancer drug gemcitabine (Gem; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme–substrate recognition between deoxycytidine kinase and GEM relies on hydrogen bonding between the 4‐NH 2 group of the nucleobase cytosine and Asp133, located in the active site of the enzyme . Chemically and enzymatically activatable GEM prodrugs have been developed by installing a protecting group onto the 4‐NH 2 group . Thus, A‐GEM was also designed by masking the same position in GEM with a boronate‐ester‐based carbamate protecting group (Figure ).…”
Section: Resultsmentioning
confidence: 99%